Curso de formación a distancia como estrategia para desarrollar el aprendizaje autodirigido en médicos de pregrado - Muñoz Cortés, Gerardo (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
The incorporation of Information and Communication Technologies (ICT) to education, is producing transformations in the teaching and learning processes; they contribute to internal undergraduate doctors recognizing the need for self-directed learning that allows them to take the initiative, formulate learning goals, identify material resources and evaluate their results. The objective of the research was to demonstrate the impact that the use of ICT has on self-directed learning, the learning style and the level of knowledge about diabetes of the IMSS undergraduate internal doctors. A mixed study was carried out: through an action research, the clinical practices of the participants were made efficient by linking the activities of the Moodle platform; with a quasi-experimental, descriptive-correlational design. We included 12 participants, from December 4 to 18, 2017. A diabetes course was designed and implemented, and pre- and post-intervention evaluations were conducted. The Felder questionnaire was applied to identify the learning style of the participants, the self-directed learning scale, a diabetes knowledge assessment test and a satisfaction survey about the course. For the statistical analysis, descriptive statistics, means comparison tests and square chi were used for association of variables. The results show registered (n = 12), 6 women (50%) and 6 men (50%), single (91.6%) with a degree (100%); with active learning styles 75%, sensory 92%, visual 75% and overall 67%; self-directed learning high level 67%, medium-high 25% and medium-low 8%; initial knowledge mean 7.25, standard deviation 1.6 and final knowledge mean 9.0, standard deviation 0.8 and satisfaction on the course, excellent 83% and good 17%. So there is a favorable impact on the internal doctors of undergraduate, who took the distance training course of diabetes, increasing their self-directed learning, in the domain of desire to learn and with changes in the learning style, favoring the visual style and decreasing the global style.

La incorporación de las Tecnologías de la Información y la Comunicación (TIC) a la educación, está produciendo transformaciones en los procesos de enseñanza y aprendizaje; permite que los médicos internos de pregrado reconozcan la necesidad de un aprendizaje autodirigido que les permita asumir la iniciativa, formular metas de aprendizaje y evaluar sus resultados. El objetivo de la investigación fue demostrar el impacto que tiene el uso de las TIC sobre el aprendizaje autodirigido, el estilo de aprendizaje y el nivel de conocimientos sobre diabetes de los médicos internos de pregrado del IMSS. Se realizó un estudio mixto con un diseño cuasiexperimental, descriptivo-correlacional y con una investigación-acción donde se hicieron eficientes las prácticas del alumno vinculándolo con las actividades de la plataforma Moodle. Se incluyeron 12 participantes, del 4 al 18 de diciembre de 2017; se diseñó e implementó un curso de diabetes con evaluaciones pre y pos-intervención. Se aplicaron: el cuestionario de Felder para identificar el estilo de aprendizaje, la escala de aprendizaje autodirigido, un examen de conocimientos sobre diabetes y una encuesta de satisfacción. Los datos se presentan en porcentajes, así como media y desviación estándar (M±DE). Los resultados muestran 6 mujeres (50%) y 6 hombres (50%), solteros (91.6%) con licenciatura (100%); con estilos de aprendizaje activo 75%, sensorial 92%, visual 75% y global 67%; presentando niveles de aprendizaje autodirigido alto 67%, medio-alto 25% y medio-bajo 8%; con un conocimiento inicial de 7.25±1.6 y un conocimiento final de 9.0±0.8; la satisfacción del curso fue excelente 83% y buena 17%. Por lo que, existe un impacto favorable en los médicos internos de pregrado que tomaron el curso de formación a distancia, aumentando su aprendizaje autodirigido, en el dominio de deseo de aprendizaje y con cambios en el estilo de aprendizaje, favoreciendo el estilo visual y disminuyendo el estilo global.
Facultad de Psicología. Maestría en Psicología
Keywords: info:eu-repo/classification/cti/4; FP-M-2018-1067; Tecnologías de la información y comunicación; Diabetes mellitus; Médico; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3590